Changing Pattern of Shingles (Herpes Zoster) in Hill Tracts: A Study among Tribal Community of Bangladesh - Islam, Ahmed Tanjimul (Delta Medical College Journal, 2020)
Background: Herpes zoster infection (shingles) is a common painful disease in Bangladesh. Changing pattern of the disease presentation can cause delayed diagnosis, inappropriate treatment, prolongation of the disease with debilitating symptoms and post herpetic neuralgia. Objective: The study was done to evaluate the different changing clinical and dermatome pattern of shingles among tribal community in Hill tracts of Bangladesh. Materials and method: This descriptive hospital based study was carried out among 74 shingles patients using simple, direct, standardized questionnaire with history, clinical and dermatological examination from July 2015 to July 2016 in Rangamati General Hospital, Rangamati, Bangladesh. Results: August to October was the vulnerable period for Shingles (75.7%) with highest number of cases found in September (32.4%). Rural area (70.2%) is vulnerable than urban area. Lumbar region (39.1%) is the commonest dermatome involved during examination. Itching was the commonest complaint (41.9%) for physician consultation and 15% cases suffered reactivation within six months in the same dermatome region. Conclusion: As changing and different pattern of manifestations are common in shingles in Hill Tracts, these are to be considered by local and consultant physicians in the total management to decrease delayed complications and reactivation. Delta Med Col J. Jul 2019 7(2): 56-60